KURSUS BIMBINGAN BELAJAR MENYENANGKAN DAN GRATIS DI SEKOLAH DASAR YAYASAN PENDIDIKAN BEERSEBA - Hotmaida Simanjuntak; Junifer Parsaoran Manurun; Desi Era Sihombing; Lasma Warni Tambunan; Febriyanti Hutasoit; Ribka Aurelia Situmorang; Ongsina Ongsina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: This study will explain about Community service is the implementation of the practice of science, technology and cultural arts directly on the community institutionally through scientific methodologies as the spread of the Tri Dharma of Higher Education and noble responsibility in an effort to develop community capabilities, so as to accelerate the rate of growth achievement of national development goals. The objectives to be achieved through community service activities are as follows: a) Increasing the speed of the process of increasing the capacity of human resources in accordance with the rate of development growth; b) Increasing the speed of community development efforts towards the establishment of a harmonious and dynamic society that is ready to take changes towards improvement and progress in accordance with socio-cultural values and norms in the life of a developing community in the life of the prevailing society; c) Increasing the speed of efforts to foster community institutions and professions in accordance with the growth rate of the modernization process in people's lives themselves; and d) To obtain feedback and input for the faculty in order to increase the relevance of education, it is necessary to have experts who have interdisciplinary and multidisciplinary abilities. It is hoped that the PKM that has been implemented can be beneficial to the community, especially to: a) Beerseba Elementary School Foundation, and especially for Beerseba Elementary School students; b) The surrounding community where students serve are residents of JL. Kaswari; c) HKBP Nommensen University; and d) Students who carry out PKM.Keywords: Course, Tutoring, Fun, Free, Elementary School.